2007
DOI: 10.1111/j.1365-2834.2007.00670.x
|View full text |Cite
|
Sign up to set email alerts
|

The Nursing Worklife Model: Extending and Refining a New Theory

Abstract: Aims  We tested a modification of Leiter and Laschinger's Nursing Worklife Model by examining the impact of structural empowerment on professional work environment factors that lead to nursing job satisfaction. Background  The original model explains how five magnet hospital practice domains described by Lake (2002) interact to influence nurses’ work lives by either contributing to or mitigating burnout. Methods  A non‐experimental design was used. Five hundred randomly selected nurses in Michigan were surveye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
85
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(100 citation statements)
references
References 27 publications
12
85
0
3
Order By: Relevance
“…In the same line of Manojlovich & Laschinger [23] and Faulkner & Laschinger [24] studies founded that once nurses are empowered, they use organizational and nursing unit domains more effectively, and resulting in greater job satisfaction. Accordingly Laschinger et al [19] founded that a strong relationship with physicians and nurses with nurse managers, especially facilitate the nurses' feeling of being empowered.…”
Section: Discussionmentioning
confidence: 99%
“…In the same line of Manojlovich & Laschinger [23] and Faulkner & Laschinger [24] studies founded that once nurses are empowered, they use organizational and nursing unit domains more effectively, and resulting in greater job satisfaction. Accordingly Laschinger et al [19] founded that a strong relationship with physicians and nurses with nurse managers, especially facilitate the nurses' feeling of being empowered.…”
Section: Discussionmentioning
confidence: 99%
“…4 Research on workplace empowerment has linked hospital environments that have empowering social structures with better nursing outcomes. 5,6 However, the influence of either magnet-hospital characteristics or workplace empowerment factors in the practice environment on adverse outcomes deemed sensitive to nursing care has not been established.…”
Section: Objectivesmentioning
confidence: 99%
“…[5][6][7] Laschinger also has joined with colleagues in testing the Nursing Worklife Model, which links organizational variables to job satisfaction and burnout in nurses. 8,9 The present study was designed to extend the work of Piazza and colleagues, 10 who found differences in empowerment between nationally certified nurses and nurses who were not certified. That small study among nurses employed in a community T he study reported here was initiated by the American Association of Critical-Care Nurses (AACN) and funded by the AACN Certification Corporation.…”
Section: Introductionmentioning
confidence: 99%